30-6(x-3)=9(x-5)

Simple and best practice solution for 30-6(x-3)=9(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30-6(x-3)=9(x-5) equation:


Simplifying
30 + -6(x + -3) = 9(x + -5)

Reorder the terms:
30 + -6(-3 + x) = 9(x + -5)
30 + (-3 * -6 + x * -6) = 9(x + -5)
30 + (18 + -6x) = 9(x + -5)

Combine like terms: 30 + 18 = 48
48 + -6x = 9(x + -5)

Reorder the terms:
48 + -6x = 9(-5 + x)
48 + -6x = (-5 * 9 + x * 9)
48 + -6x = (-45 + 9x)

Solving
48 + -6x = -45 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
48 + -6x + -9x = -45 + 9x + -9x

Combine like terms: -6x + -9x = -15x
48 + -15x = -45 + 9x + -9x

Combine like terms: 9x + -9x = 0
48 + -15x = -45 + 0
48 + -15x = -45

Add '-48' to each side of the equation.
48 + -48 + -15x = -45 + -48

Combine like terms: 48 + -48 = 0
0 + -15x = -45 + -48
-15x = -45 + -48

Combine like terms: -45 + -48 = -93
-15x = -93

Divide each side by '-15'.
x = 6.2

Simplifying
x = 6.2

See similar equations:

| 4(x-11)+6x=36 | | 3-3(x+6)=3 | | 5x+6(x-0)=11 | | 2y^3+5y^2+2y= | | 6x+6(x-4)=24 | | 20(x-3)+2x=56-2(x-4) | | 4-6(x+5)=4 | | 4d+2(d+3)=-3(d-2) | | m+m+1+m+2=57 | | 5x+3=21-4x | | 4-8x=24-4x | | x/2+14=46 | | 9x-4=5x+7 | | 8n-1=5n-10 | | 69*2-x=45 | | 6x+3=91-5x | | 10+2x=15+3x | | 86-5x=13x+16 | | z^4-8z+15=0 | | 14+5x=22+6x | | 3*3+4=16 | | p^2-13p+18=0 | | 5x-3=11x-4 | | 1-9x=55-3x | | 5x-4y=-28 | | 5x+23=10x-67 | | 5x+23=10x-68 | | 75-3x=10x-4x | | z^4-8z^2+15=0 | | 6x+12.3-10.2=1.5 | | Z-y-b= | | -p-1=-21 |

Equations solver categories